Extent of Use of Information and Communications Technology and Inventory Management in the Nigerian Brewery Industry - Olusegun Timothy Odesola; Grace Oluyemisi Akinola (Journal of Information Systems Engineering and Business Intelligence, 2018)
This paper examined the extent of usage of Information and Communications Technology (ICT) for inventory management in the Nigerian brewery industry; investigated the level of adoption of ICT in the inventory management phases; and the effect of the extent of ICT usage on its adoption by firms in the industry. Primary data formed the methodology of the study. The analysis of data collected was done using descriptive (tables and percentages) and inferential statistics. The results showed that majority of the respondents were using ICT tools and its associated components in their inventory management. It was revealed that the extent of ICT usage had significant effect on its adoption for inventory management by firms in the industry. Based on these findings, the study concluded that ICT is fully deployed and adopted to a very great extent for inventory management in the Nigerian brewery industry and that its adoption and usage in the brewery industry was influenced by its extent of use. The study recommends that firms in the industry should make judicious use of the identified ICT usage by adopting ICT solutions for their operations to boost the efficiency and effectiveness of their operations.